2023
DOI: 10.1021/acs.nanolett.3c01044
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Organic Radical Spin Source

Constantinos Nicolaides,
Fadwat Bazzi,
Evangelos Vouros
et al.

Abstract: Organic radicals have long been suggested as candidates for organic magnets and components in organic spintronic devices. Herein, we demonstrate spin current emission from an organic radical film via spin pumping at room temperature. We present the synthesis and the thin film preparation of a Blatter-type radical with outstanding stability and low roughness. These features enable the fabrication of a radical/ferromagnet bilayer, in which the spin current emission from the organic radical layer can be reversibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“… Amdur et al, (2022) investigated this control to discover a room temperature molecular qubit, highlighting the potential of molecular electronic spins as a novel platform for qubit structure and control. Additionally, the study by Nicolaides et al. (2023) provides insights into spin pumping from organic radical films, presenting another avenue to explore.…”
Section: The Quantum-based Magnetoreception Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“… Amdur et al, (2022) investigated this control to discover a room temperature molecular qubit, highlighting the potential of molecular electronic spins as a novel platform for qubit structure and control. Additionally, the study by Nicolaides et al. (2023) provides insights into spin pumping from organic radical films, presenting another avenue to explore.…”
Section: The Quantum-based Magnetoreception Mechanismmentioning
confidence: 99%
“…Amdur et al, (2022) investigated this control to discover a room temperature molecular qubit, highlighting the potential of molecular electronic spins as a novel platform for qubit structure and control. Additionally, the study by Nicolaides et al (2023) provides insights into spin pumping from organic radical films, presenting another avenue to explore. They demonstrated spin current emission from a Blattertype radical with outstanding stability and low roughness, indicating the possibility of realizing spin pumping even in the absence of long-range ferromagnetic order (Nicolaides et al, 2023).…”
Section: The Alternative Radical-pair Mechanism: the Unsuspected In-v...mentioning
confidence: 99%
See 1 more Smart Citation
“…65 Thin films based on Blatter-type radicals can act as metal-free spin-sources in purely organic spintronic devices. 66 Blatter radicals can also be used as polarizing agents of Overhauser DNP for high-field MAS-DNP. 67,68 The application of Blatter radicals in cutting-edge devices requires the development of "structure−activity" relationships.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1D ferromagnetism and antiferromagnetism have been reported ,,, along with two examples of magnetic-bistability associated with a first-order structural phase transition. , Blatter radicals have been used in chemical synthesis as initiators in controlled polymerizations, as ligands in coordination complexes with paramagnetic metals and metal–organic frameworks (MOFs), and as building units in diradicals and biradicaloids. ,, Their optical properties stem from their low-lying SOMO orbital and include weak fluorescence, photodetection, , and liquid crystalline photoconduction. Blatter radicals have also been incorporated in electroactive polymers as components of purely all-organic batteries. ,− It has been demonstrated that they can form stable thin films without significant degradation while retaining their paramagnetic character. , Several recent studies , have examined the Blatter radical/inorganic “spinterface” and their possible applications in spintronic devices . Thin films based on Blatter-type radicals can act as metal-free spin-sources in purely organic spintronic devices . Blatter radicals can also be used as polarizing agents of Overhauser DNP for high-field MAS-DNP. , …”
Section: Introductionmentioning
confidence: 99%